```data Btree a = Leaf a | Fork (Btree a) (Btree a) deriving (Show, Eq)

foo = Fork (Fork (Fork (Fork (Leaf 'a') (Leaf 'b')) (Leaf 'c')) (Leaf 'd')) (Leaf 'e')

size :: Btree a -> Int
size (Leaf x) = 1
size (Fork xt yt) = size xt + size yt

height :: Btree a -> Int
height (Leaf x) = 0
height (Fork xt yt) = 1 + (height xt) `max` (height yt)

flatten :: Btree a -> [a]
flatten (Leaf x) = [x]
flatten (Fork xt yt) = flatten xt ++ flatten yt

makeBtree :: [a] -> Btree a
makeBtree [x] = (Leaf x)
makeBtree xs = Fork (makeBtree (take m xs)) (makeBtree (drop m xs))
where m = (length xs) `div` 2

bar = makeBtree [1..4]

mapBtree :: (a -> b) -> Btree a -> Btree b
mapBtree f (Leaf x) = Leaf (f x)
mapBtree f (Fork xt yt) = Fork (mapBtree f xt) (mapBtree f yt)

const' k = \x -> k

foldBtree :: (a -> b) -> (b -> b -> b) -> Btree a -> b
foldBtree f _ (Leaf x) = f x
foldBtree f g (Fork xt yt) = g (foldBtree f g xt) (foldBtree f g yt)

size' = foldBtree (const 1) (+)
height' = foldBtree (const 1) (\x y -> (x `max` y) + 1)

f # g = \x y -> f (g x y)

height'' = foldBtree (const 1) (succ # max)

flatten' = foldBtree (\x -> [x]) (++)

flatten'' = foldBtree (: []) (++)

mapBtree' f = foldBtree (\x -> (Leaf (f x))) Fork

mapBtree'' f = foldBtree (Leaf . f) Fork

data RoseTree a = Node a [RoseTree a] deriving (Show,Eq)

x = Node 5 [Node 1 [], Node 2 [Node 3 [], Node 4 [Node 5 []]]]

fringe (Node x []) = [x]
fringe (Node _ xs) = concat \$ map fringe xs

flattenRoseTree (Node x []) = [x]
flattenRoseTree (Node x xs) = x:(concat \$ map flattenRoseTree xs)

sumRoseTree (Node x []) = x
sumRoseTree (Node x xs) = x + (sum \$ map sumRoseTree xs)

foldRoseTree f g (Node x []) = f x
foldRoseTree f g (Node x xs) = g x (map (foldRoseTree f g) xs)

flattenRoseTree' = foldRoseTree (:[]) (\x xs -> x : (concat xs))

fringe' = foldRoseTree (:[]) (\_ xs -> concat xs)

sumRoseTree' = foldRoseTree id (\x xs -> x + (sum xs))

mapRoseTree' f = foldRoseTree (\x -> Node (f x) []) (\x xs -> Node (f x) xs)

mapRoseTree'' f = foldRoseTree ((`Node` []) . f) (\x xs -> Node (f x) xs)
```